2007
DOI: 10.1186/1471-2393-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Use pattern of maternal health services and determinants of skilled care during delivery in Southern Tanzania: implications for achievement of MDG-5 targets

Abstract: BackgroundAlmost two decades since the initiation of the Safe motherhood Initiative, Maternal Mortality is still soaring high in most developing countries. In 2000 WHO estimated a life time risk of a maternal death of 1 in 16 in Sub- Saharan Africa while it was only 1 in 2800 in developed countries. This huge discrepancy in the rate of maternal deaths is due to differences in access and use of maternal health care services. It is known that having a skilled attendant at every delivery can lead to marked reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
300
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(368 citation statements)
references
References 16 publications
56
300
11
1
Order By: Relevance
“…On the other hand, women who live within 30 min walking distance from the health facility were more likely to use ANC. Previous studies in Ethiopia and other African countries have also shown an association between ANC utilization and proximity to a health facility [15,7,20,31,[33][34][35]. The distance from health facilities may incur them extra expense for transportation costs which in turn could hinder them from receiving ANC services.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, women who live within 30 min walking distance from the health facility were more likely to use ANC. Previous studies in Ethiopia and other African countries have also shown an association between ANC utilization and proximity to a health facility [15,7,20,31,[33][34][35]. The distance from health facilities may incur them extra expense for transportation costs which in turn could hinder them from receiving ANC services.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers (Barber, 2006;Bloom, et al, 1999;Kabakyenga et al, 2012;Mpembeni et al, 2007) have highlighted the positive relationship between the quantity of ANC (measured in terms of number of visits) and women's use of institutional delivery care. Our findings underscore the importance of the counseling that women receive during these visits.…”
Section: Discussionmentioning
confidence: 99%
“…Because the clinical and counseling content of ANC has been shown to influence care-seeking during childbirth (Barber 2006;Bloom, Lippeveld, & Wypij, 1999;Mpembeni et al, 2007), a composite variable was developed to summarize the counseling provided to women during their ANC visits. The BP/CR Counseling Index was based on whether women reported that, during any of their ANC visits, they were advised to deliver at a health facility; advised about danger signs during pregnancy and delivery; and advised on any of the following delivery preparations: saving money, arranging for transport, discussing delivery plans with family members, or identifying a blood donor.…”
Section: Variables In the Studymentioning
confidence: 99%
“…violence, unwanted pregnancy and human immunodeficiency virus (HIV) infection [4–7]. However, men can also play a positive role, and men’s involvement in pregnancy and childbirth has been shown to benefit the health of mothers and newborns [1,813]. Men’s involvement in reproductive health can also enhance gender equality and empower individual women to make their own decisions [14,15].…”
Section: Introductionmentioning
confidence: 99%